Bacteriological Etiology of Empyema Thoracis Patients Admitted in a Tertiary Care Hospital (Bangladesh Medical Journal, 2024)
Empyema thoracis is the most common complication of pneumonia and is associated with severe morbidity and mortality. Management of empyema thoracis is complex and needs a multimodal approach. Antibiotic therapy is very crucial in management of empyema thoracis and epidemiological data is essential to ensure appropriate antibiotic therapy. This study aimed to explore the bacteriological profile of empyema thoracis in a tertiary care hospital. This cross-sectional study was carried on 30 patients admitted in the Department of Medicine and Department of Respiratory Medicine, Sir Salimullah Medical College and Mitford Hospital (SSMC & MH), Dhaka over a period of six months (March to September 2021). Mean age of the patients was 38±10.94 (SD) years and male–female ratio was 2:1 (66.7% male). The most common symptoms were found cough (86.7%) and fever (83.3%) including major presenting symptoms expectoration (76.7%) and chest pain (70.0%); other symptoms were loss of appetite (50.0%), malaise (46.7%) and hemoptysis (10.0%). The major etiology was the thoracic empyema (56.7%) followed by pneumonia (16.67%), lung abscess (10.0%), liver abscess (6.7%), lung cancer (3.3%), secondary infection (3.3%) and undetermined cases responding to antibiotics (3.3%). Bacteriological profile showed that majority of the cases (56.7%) were Mycobacterium Tuberculosis; others cases were S. aureus (6.7%), S. pyogen (6.7%), E. coli (3.3%), Klebsiella (3.3%) and Pseudomonas (6.7%). It was concluded from the study, more than half of empyema thoracis was etiologically tubercular.Bangladesh Med J. 2023 Sept; 52(3): 27-34